EXAMINING RISK MANAGEMENT PRACTICES AND CORPORATE GOVERNANCE IN CITIGROUP, GOLDMAN SACHS AND JP MORGAN - lu, chengen (2009)
The President of the United States, Obama described the subprime crisis as “the worst financial crisis since the Great Depression”. So how a crisis like this could have happened? The crisis provides food for thoughts on the issues of financial organizations’ risk management and corporate governance. This dissertation examines bank’ risk management and corporate governance under three themes, they are Theme 1: CRO and Risk committees, Theme 2: Risk measurement and mitigation, and Theme 3: Compensation Policy and Board Composition